AKUNTANSI PAJAK DAN RAHMATAN LIL ALAMIN: UPAYA KEPATUHAN PAJAK KARBON PADA INDUSTRI KERTAS - Aristantia, Selvia Eka (Jurnal Akuntansi Kompetif, 2024)
This study aims to review the internalization of Islamic values ​​in an effort to meet carbon tax compliance. This study was conducted in one of the paper industries in East Java. In its business process, this company produces carbon emissions. To answer the formulation of the problem, the researcher used a qualitative method with a case study approach. After conducting a series of analyses of data collection methods and data analysis, it can be seen that business actors maintain professional responsibility by taking part in protecting the environment. Business actors believe that protecting the environment is everyone's responsibility, especially for Muslims. Business actors believe that the value of rahmatan lil alamin is the role of the caliph that must be carried out by efforts to protect the environment through clean business processes. The industry is preparing to meet carbon tax compliance by replacing coal energy resources with environmentally friendly technology. Tax accounting records this process as a cost for managing production waste. Suggestions for business actors are to analyze carbon tax regulations and policy trends and implement a periodic emission monitoring and measurement system to manage more detailed emission data. Good coordination is needed between the government, industry, and society to ensure the successful implementation of this policy.